(untitled) (Proceeding Of Sari Mulia University Midwifery National Seminars, 2024)
Background: Pregnancy is a natural process that occurs physiologically. The pregnancy period is a time when the mother experiences physical and psychological changes during pregnancy and the increase in hormones, changes in posture, enlargement of the size of the uterus makes pregnant women often experience back pain, especially the peak during the third trimester of pregnancy. According to WHO, the incidence of back pain for pregnant women in developing countries is still high, which is 33%, in Indonesia as many as 60-70% of pregnant women experience back pain and in PMB ARYA from November - January 2024 there are 17 third trimester pregnant women who experience back pain. Objective: To determine the effect of Maryam Gymnastics on back pain of third trimester pregnant women at PMB ARYA Banjarbaru City. Methods: This study uses Pre-Experimental research type with one group pretest-posttest design technique. The population in this study was 17 pregnant women with back pain and the sampling technique used a total sampling technique of 17 people. Data collection using questionnaires as well as observation sheets and data analysis using the Wilcoxon Test. Results: The results of the study of 17 respondents based on age, the majority of pregnant women were not at risk as many as 14 people (82%), light activity as many as 17 people (100%), not excessive weight gain as many as 11 people (65%) BMI of normal pregnant women as many as 9 people (53%). The results of data analysis of the Effect of Maryam Gymnastics on Back Pain of Third Trimester Pregnant Women in PMB ARYA using the Wilcoxon test obtained a significant t value of 0.000 (Sig < 0.05). Conclusion:Maryam exercises performed on pregnant women can relax muscles, improve blood circulation, reduce stress and relax pregnant women so that Maryam exercises have a significant influence on changes in third trimester pregnant women’s back pain.